Diagnosis and molecular characterization of three allexiviruses infecting garlic crop in Saudi Arabia: New allexiviruses infecting garlic - Amir, Muhammad; Amer, Mahmoud; Khalid, Zaheer; Zaman, Muhammad; Al-Saleh, Mohammed (Cellular and Molecular Biology, 2025)
Forty-four samples of garlic plants showing virus-like symptoms were collected, during the growing season (2021-2022) from different locations in Qassim province, Saudi Arabia. These samples were analyzed by ELISA against the important Allium allexiviruses including garlic virus A (GarV-A), garlic virus B (GarV-B), garlic virus C (GarV-C), and Shallot virus X (ShVX). The obtained results showed that 22/44 (50%) samples were found to be infected with one of the tested viruses. Mixed infections were detected in 13/22 samples (59.1%) with more than one virus. However, 13.6%, 0% and 27.2% were detected as single infection with GarV-A, GarV-B and GarV-C respectively. RT-PCR amplification with general allexiviruses primer (750 bp) and specific primers for GarV-A (1330 bp), GarV-B (1216 bp) and GarV-C (1557 bp) were used to detect the respective viruses. The phylogenetic tree and nucleotide sequence analysis of one of each GarV-A (OQ397541), GarV-B (OQ397542) and GarV-C (OQ397543) with general primer for allexiviruses while one isolate of each GarV-A (ON155441), GarV-B (OR343811) and two isolates of GarV-C (ON155445, and ON155446) with specific primers showed their similarity with their respective viruses from GenBank. In host range study, Chenopodium amaranticolor, Nicotiana benthamiana, N. tabacum and Allium cepa expressed necrotic lesions, mosaic and yellowing symptoms respectively against GarV-A, GarV-B and GarV-C. To our knowledge, this is the first report of GarV-A, GarV-B, and GarV-C in Saudi Arabia.